Conflicts of interest in dialysis: A barrier to policy reforms. Issue 1 (3rd January 2020) - Glickman, Aaron; Lin, Eugene; Berns, Jeffrey S.
Abstract: Conflicts of interest involving physicians are commonplace in the US, occurring across many different specialties and subspecialties in a variety of clinical settings. In nephrology, two important scenarios in which conflicts of interest arise are dialysis facility joint venture (JV) arrangements and financial participation in End‐stage Kidney Disease Seamless Care Organizations (ESCOs). Whether conflicts of interest occurring in either of these settings influence decision‐making or patient care outcomes is not known due to a lack of transparent, publicly available information, and opportunities to conduct independent study. We discuss possible benefits and risks of nephrologist's financial participation in JVs and ESCOs and possible mechanisms for disclosure and reporting of such arrangements as well as risk mitigation.